Analysis of Early Literacy Practices Based on Social Inclusion in Palembang - Lestari, Maya; Kurniati, Euis (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – The purpose of this study is to explore children's literacy activities at home that involve parenting in Indonesia from a social inclusion perspective. Design/methods/approach – This study uses a qualitative research method. Analyzing the results of interviews conducted with four parents and teachers in Palembang, Indonesia, and using a critical theory perspective as the basis for the analysis. Findings – In the setting of Early Childhood Education and Care (ECEC), literacy practices are not only carried out at school but also in the home and community. Based on the findings that we conducted on four parents and teachers in Palembang, the practice of early literacy at home is very diverse. The practice of early literacy at home is also still experiencing problems, especially in the provision of media that supports children's literacy interests, especially in the fields of reading and numeracy. Research implications/limitations – From an early age, it is important to synergize the roles of families, institutions, and the government in an effort to support the practice of early literacy based on social inclusion. Practical implications – This study has deep implications for realizing the interest in children's literacy in this country. Originality/value – his study contributes in the form of understanding literacy practices in early childhood education. Paper type Research paper